2022
DOI: 10.1111/1462-2920.16305
|View full text |Cite
|
Sign up to set email alerts
|

The catalase‐peroxidase PiCP1 plays a critical role in abiotic stress resistance, pathogenicity and asexual structure development in Phytophthora infestans

Abstract: Catalase‐peroxidase is a heme oxidoreductase widely distributed in bacteria and lower eukaryotes. In this study, we identified a catalase‐peroxidase PiCP1 (PITG_05579) in Phytophthora infestans. PiCP1 had catalase/peroxidase and secretion activities and was highly expressed in sporangia and upregulated in response to oxidative and heat stresses. Compared with wild type, PiCP1‐silenced transformants (STs) had decreased catalase activity, reduced oxidant stress resistance and damped cell wall integrity. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…29,30 Many oxidoreductase genes were found to be highly expressed during fungal infection process, but the functions of most of them remain unknown. 31,32 Our results indicated that VdOrlp was highly expressed when fungal hyphae contacted plant tissue but exhibited low expression levels on artificial media. These results suggest that VdOrlp specifically functions during the infection process.…”
Section: Discussionmentioning
confidence: 78%
“…29,30 Many oxidoreductase genes were found to be highly expressed during fungal infection process, but the functions of most of them remain unknown. 31,32 Our results indicated that VdOrlp was highly expressed when fungal hyphae contacted plant tissue but exhibited low expression levels on artificial media. These results suggest that VdOrlp specifically functions during the infection process.…”
Section: Discussionmentioning
confidence: 78%